Analysis of Needs Design of Cognitive Conflict-Based Teaching Materialis Integrated Augmented Reality on Material Sound Wave - Anelfia, Syifa Chaerunisa; Mufit, Fatni (Universitas Negeri Padang, 2023)
Teaching materials are a very important component in the learning process. The completeness of teaching materials is the main factor in increasing students' understanding of concepts and can reduce student misconceptions. Teaching materials in schools are currently still very limited and there are no teaching materials that can overcome students' misconceptions and are not yet integrated with technology. One solution to overcome this is by developing cognitive conflict-based teaching materials integrated with Augmented Reality technology. This study aims to present the results of the needs analysis of cognitive conflict teaching materials integrated with augmented reality (AR) sound wave material. This research is a descriptive research, which was conducted at SMA N 15 Padang. The research subjects were 36 students and 3 physics teachers. The instrument of this research is a questionnaire to the teacher, questionnaire to students and journal analysis sheets. Data were analyzed quantitatively and qualitatively. The results of the study show that teachers still experience many obstacles when implementing an independent curriculum and the need for special training in implementing an independent curriculum. The teaching materials used by students are still limited and there are no teaching materials that can overcome students' misconceptions and the teaching materials are not yet integrated with technology. The level of students' understanding of sound waves is still low and there are misconceptions. Therefore, from the results of preliminary research it is necessary to develop cognitive conflict-based physics teaching materials that integrate augmented reality technology.